Facile synthesis and characterization of multi-walled carbon nanotubes decorated with hydroxyapatite from cattle horns for adsorptive removal of fluoride - Ojok, Walter; Bolender, James P; Wasswa, John; Ntambia, Emmanuel; Wanasolo, William; Moodley, Brenda (Heliyon, 2023)
Developing a new adsorbent for fluoride removal from cattle horn waste materials by a facile chemical method has shown great potential for fluoride removal. This paper reports the synthesis of multi-walled carbon nanotubes decorated with hydroxyapatite from cattle horns (MWCNT- CH) using a facile chemical method. Characterization studies using standard techniques showed that the composite is mesoporous with a rough morphology and contained MWCNTs uniformly encapsulated by the hydroxyapatite forming a crystalline MWCNT-CH composite. Optimization of fluoride adsorption by the as-synthesized composite using Response Surface Methodology (RSM) showed that a maximum fluoride removal efficiency of 80.21% can be attained at initial fluoride concentration = 10 mg/L, pH = 5.25, adsorbent dose = 0.5 g and a contact time of 78 min. ANOVA indicates contribution of the process variables in descending order as pH > contact time > adsorbent dose > initial fluoride concentration. Langmuir isotherm (R2 = 0.9991) best described the process, and the maximum adsorption capacity of fluoride onto the as-synthesized MWCNT-CH composite was 41.7 mg/g. Adsorption kinetics data were best fitted in the pseudo-second-order kinetic model (R2 = 0.9969), indicating chemisorption. The thermodynamic parameter (H = 13.95 J/mol and S = 65.76 J/mol/K) showed that fluoride adsorption onto the MWCNT-CH composite was a spontaneous, endothermic, and entropy-driving process. Moreover, the adsorption mechanism involves ion exchange, electrostatic interaction, and hydrogen bonding. Fluoride was successfully desorbed (using 0.1 M NaOH) from the composite in four cycles, retaining fluoride removal efficiency in the fourth cycle of 57.3%.
Keywords: Cattle horn; Fluoride adsorption; Hydroxyapatite Kinetics; Multi-walled carbon nanotubes; Response surface methodology